Hypoglycemic and hepatoprotective effect of Rhizophora mucronata and Avicennia marina against streptozotocin-induced diabetes in male rats - Ali Al-Jaghthmi, Obidallah Hamdan; Abu Zeid, Isam ELDin Mohamed ELAmin (Journal of Advanced Veterinary and Animal Research, 2020)
Objectives: Aqueous extracts of Rhizophora mucronata and Avicennia marina leaves were investigated for their hepatoprotective potential in diabetic rats. Materials and methods: One hundred twenty male albino rats were randomly assigned to eight equal groups (n = 15). The first group (control) comprised normal healthy rats, while the second to fifth groups were intraperitoneally injected with a single dose of streptozotocin (STZ) [60 mg/ kg body weight (BW)] for induction of diabetes. Group 2 was kept as positive diabetic control, while groups 3–5 were orally treated with aqueous extracts of R. mucronata (400 mg/kg BW), A. marina (400 mg/kg BW) and with a combination of ½ a dose of the two plants, respectively, for six weeks. Groups 6–8 were non-diabetic rats that orally received aqueous extracts of R. mucronata (400 mg/kg BW), A. marina (400 mg/kg BW), and a combination of ½ a dose of the two plants, respectively, for 6 weeks. Results: STZ-induced diabetic rats showed a significant reduction in serum glucose and liver enzymes, increased serum insulin, Homeostasis Model Assessment of β-cells (HOMA-β), and Homeostasis Model Assessment of Insulin Resistance (HOMA-IR). Histopathological and immunohistochemical examinations of the liver revealed improved pathologic criteria in the plant extract treated diabetic rats compared with the remarkable changes which had been seen in STZ-induced diabetic rats. Conclusion: This study suggests that the aqueous extract of R. mucronata or its combination with A. marina showed potent hypoglycemic and hepatoprotective effects for liver dysfunction, as well as histopathological and immunohistochemical changes in the liver of STZ-induced diabetic rats. J. Adv. Vet. Anim. Res., 7(1): 177-185, March 2020